Librarians’ Experiences of the Teaching Role: Grounded in Campus Relationships - Julien, Heidi; Pecoskie, Jennifer (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Fifty-six semi-structured interviews were conducted in academic and public libraries across Canada in a study examining librarians’ experience of the teaching role. This paper focuses on participants’ revelations about the complex relationship between instructional librarians and teaching faculty. These relationships are examined through role theory and symbolic interactionism perspectives. Cinquante-six entrevues semi-structurées ont été menées dans les milieux des bibliothèques universitaires et publiques à l’échelle du Canada dans le cadre d’une étude visant à examiner l’expérience des bibliothécaires du rôle d’enseignement. Le présent article se concentre sur les révélations des participants au sujet de la relation complexe qui existe entre les bibliothécaires qui enseignent et les membres du corps professoral. Ces relations sont examinées par l’entremise de la théorie du rôle et des perspectives interactionnistes symboliques.